Apolipoprotein L1 Variant Associated with Increased Susceptibility to Trypanosome Infection - Bart Cuypers (American Society for Microbiology, 2016)
ABSTRACT African trypanosomes, except Trypanosoma brucei gambiense and Trypanosoma brucei rhodesiense, which cause human African trypanosomiasis, are lysed by the human serum protein apolipoprotein L1 (ApoL1). These two subspecies can resist human ApoL1 because they express the serum resistance proteins T. b. gambiense glycoprotein (TgsGP) and serum resistance-associated protein (SRA), respectively. Whereas in T. b. rhodesiense, SRA is necessary and sufficient to inhibit ApoL1, in T. b. gambiense, TgsGP cannot protect against high ApoL1 uptake, so different additional mechanisms contribute to limit this uptake. Here we report a complex interplay between trypanosomes and an ApoL1 variant, revealing important insights into innate human immunity against these parasites. Using whole-genome sequencing, we characterized an atypical T. b. gambiense infection in a patient in Ghana. We show that the infecting trypanosome has diverged from the classical T. b. gambiense strains and lacks the TgsGP defense mechanism against human serum. By sequencing the ApoL1 gene of the patient and subsequent in vitro mutagenesis experiments, we demonstrate that a homozygous missense substitution (N264K) in the membrane-addressing domain of this ApoL1 variant knocks down the trypanolytic activity, allowing the trypanosome to avoid ApoL1-mediated immunity. IMPORTANCE Most African trypanosomes are lysed by the ApoL1 protein in human serum. Only the subspecies Trypanosoma b. gambiense and T. b. rhodesiense can resist lysis by ApoL1 because they express specific serum resistance proteins. We here report a complex interplay between trypanosomes and an ApoL1 variant characterized by a homozygous missense substitution (N264K) in the domain that we hypothesize interacts with the endolysosomal membranes of trypanosomes. The N264K substitution knocks down the lytic activity of ApoL1 against T. b. gambiense strains lacking the TgsGP defense mechanism and against T. b. rhodesiense if N264K is accompanied by additional substitutions in the SRA-interacting domain. Our data suggest that populations with high frequencies of the homozygous N264K ApoL1 variant may be at increased risk of contracting human African trypanosomiasis.